Computed Tomography-Based Patient-Specific Instrumentation Loses Accuracy with Significant Varus Preoperative Misalignment - León-Muñoz, Vicente Jesús; López-López, Mirian; Lisón-Almagro, Alonso José; Martínez-Martínez, Francisco; Santonja-Medina, Fernando (The Journal of Knee Surgery, 2020)
Patient-specific instrumentation (PSI) has been introduced to simplify and make total knee arthroplasty (TKA) surgery more precise, effective, and efficient. We performed this study to determine whether the postoperative coronal alignment is related to preoperative deformity when computed tomography (CT)-based PSI is used for TKA surgery, and how the PSI approach compares with deformity correction obtained with conventional instrumentation. We analyzed pre- and post-operative full length standing hip-knee-ankle (HKA) X-rays of the lower limb in both groups using a convention > 180 degrees for valgus alignment and < 180 degrees for varus alignment. For the PSI group, the mean (± SD) pre-operative HKA angle was 172.09 degrees varus (± 6.69 degrees) with a maximum varus alignment of 21.5 degrees (HKA 158.5) and a maximum valgus alignment of 14.0 degrees. The mean post-operative HKA was 179.43 degrees varus (± 2.32 degrees) with a maximum varus alignment of seven degrees and a maximum valgus alignment of six degrees. There has been a weak correlation among the values of the pre- and post-operative HKA angle. The adjusted odds ratio (aOR) of postoperative alignment outside the range of 180 ± 3 degrees was significantly higher with a preoperative varus misalignment of 15 degrees or more (aOR: 4.18; 95% confidence interval: 1.35–12.96; p = 0.013). In the control group (conventional instrumentation), this loss of accuracy occurs with preoperative misalignment of 10 degrees. Preoperative misalignment below 15 degrees appears to present minimal influence on postoperative alignment when a CT-based PSI system is used. The CT-based PSI tends to lose accuracy with preoperative varus misalignment over 15 degrees.
Keywords: osteoarthritis; knee; total knee arthroplasty; patient-specific instrumentation; alignment; radiological assessment